A lead-free brass alloy and a method for producing the same
By adjusting the composition and process of lead-free brass alloys, Bi-In free-machining phase and NiB compound are formed, solving the problem of easy cracking of bismuth brass alloys during cold and hot working. This achieves a balance between the machinability and stress relaxation resistance of high-precision lens parts, making them suitable for high-precision optical instruments.
Patent Information
- Application Number
- CN202410213330.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-02-27
- Publication Date
- 2026-11-06
- Estimated Expiration
- 2044-02-27
AI Technical Summary
Existing bismuth brass alloys are prone to cracking during cold and hot working processes, and it is difficult to balance machinability and elasticity, thus failing to meet the high precision and stress relaxation resistance requirements of lens parts.
By adjusting the composition ratio of copper, bismuth, nickel, boron, and indium, a Bi-In free-machining phase and a NiB compound are formed. Combined with specific smelting, casting, extrusion, annealing, and drawing processes, the microstructure and properties of the material are optimized.
It achieves a balance between excellent machinability, stress relaxation resistance, and elasticity of the material, making it suitable for applications in high-precision optical instruments.
Smart Images

Figure CN117926070B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of copper alloy technology, specifically to a lead-free brass alloy and its preparation method. Background Technology
[0002] In recent years, optical instruments, as indispensable tools in resource exploration, space exploration, scientific experiments, and various aspects of social life, have seen a continuous expansion in market size, while performance requirements have also gradually increased. In particular, the lens components used in conjunction with optical instruments are trending towards smaller, thinner, and lighter designs, thus placing higher demands on the precision between the lens and the copper module gasket. Not only must the dimensional tolerance of the copper module gasket be controlled within the micrometer range of 0.001 mm, but the gasket surface must also achieve excellent smoothness and flatness to ensure a perfect fit during lens assembly. Considering the tightness of the assembly between the copper module gasket and the lens to prevent loosening and lens detachment during long-term use, the gasket material must possess good stress relaxation resistance and elasticity.
[0003] Currently, bismuth brass, as a commercially available lead-free and environmentally friendly brass product, is gradually replacing some lead brass in numerous industries such as electronics, electrical engineering, and hardware. It can also be used in copper module gaskets. Bismuth brass primarily achieves good machinability by forming bismuth particles or thin film particles, which lubricate and break chips during material processing. However, although bismuth brass has comprehensive properties close to lead brass, it has an extremely high tendency to become brittle and is prone to cracking during hot and cold working processes. While these problems can be mitigated by reducing the amount of bismuth added, a decrease in bismuth content significantly reduces the material's machinability. Therefore, in current technology, it is impossible to achieve both optimal hot and cold working performance and good machinability in bismuth brass.
[0004] For example, the high-performance bismuth brass alloy material for mobile phone lenses in Chinese invention application CN115198137A involves high extrusion temperatures and intermediate annealing, which exacerbates the aggregation of Bi elements into a thin film. This results in two issues: firstly, the material's machinability is insufficient for micron-level precision machining; secondly, the high-temperature intermediate annealing causes the material's elastic properties and stress relaxation resistance to fail to meet requirements. Similarly, the lead-free free-machining bismuth brass alloy material for mobile phone lenses in Chinese invention application CN113337754A also involves high-temperature softening annealing in its intermediate process, with a softening temperature far exceeding the bismuth melting point of 271°C. While this improves the material's processing plasticity, it negatively impacts machinability. Furthermore, the material's yield strength is low after recrystallization softening annealing, and its elastic properties also fail to meet the requirements for gaskets.
[0005] In summary, improvements to bismuth brass materials are needed. Summary of the Invention
[0006] The first technical problem to be solved by the present invention is to provide a lead-free brass alloy that has excellent machinability, stress relaxation resistance and elasticity, in light of the above-mentioned technical status.
[0007] The second technical problem to be solved by the present invention is to provide a method for preparing a lead-free brass alloy in light of the above-mentioned technical status.
[0008] The technical solution adopted by the present invention to solve the first technical problem mentioned above is: a lead-free brass alloy, characterized in that: the chemical composition of the lead-free brass alloy by mass percentage is: Cu: 53-60%; Bi: 0.1-0.8%; Ni: 0.05-1.8%; B: 0.001-0.08%; In: 0.03-0.15%, with the balance being Zn and unavoidable impurities.
[0009] Preferably, the chemical composition of the lead-free brass alloy is as follows (by mass percentage): Cu: 55-58%; Bi: 0.2-0.6%; Ni: 0.1-1.5%; B: 0.001-0.05%; In: 0.05-0.1%, with the balance being Zn and unavoidable impurities.
[0010] The lower limit for Cu content is controlled at 53%. If it is below this limit, the remaining Zn content will be too high, resulting in excessive CuZn electron compounds. The β and γ phases can easily increase the brittleness of the material, making it difficult to meet the requirements of cold deformation processing such as stretching. The upper limit for Cu content is controlled at 60%. If it is above this limit, the amount of α phase will increase. The α phase is soft and has high plasticity. Although it is beneficial for cold deformation plastic processing, it is prone to sticking to the cutting tool during machining, which is not conducive to cutting performance and cannot meet the requirements of high-speed precision lathe machining. Therefore, considering the balance between material processing plasticity and cutting performance, the Cu content is controlled in the range of 53% to 60%. To obtain a better balance between processing plasticity and cutting performance, the Cu content is preferably in the range of 55% to 58%.
[0011] Bi, as a free-machining element, has extremely low solubility in the matrix and is generally distributed in grain boundaries. Although increasing the Bi content is beneficial to machinability, it also significantly increases the material's hot brittleness and tendency to self-crack, while negatively impacting elastic properties and stress relaxation resistance. To obtain good cold and hot working plasticity, elasticity, and stress relaxation resistance, the upper limit of the Bi content is controlled at 0.8%, preferably 0.6%.
[0012] Ni has extremely high solid solubility in the Cu matrix, forming a continuous solid solution that improves the material's mechanical properties, ductility, and cold deformation processing performance. Ni provides solid solution strengthening and reacts with boron (B) to form NiB compounds. Under certain heat treatment conditions, these NiB compounds precipitate from the matrix, providing precipitation strengthening and improving yield strength and elastic properties, ensuring good compactness during assembly of finished parts. B also promotes the formation of more nucleation sites in the matrix, facilitating the inclusion of more free-machining phases and indirectly improving machinability. However, excessive Ni content increases the material's resistance to hot deformation, requiring higher extrusion temperatures. Higher extrusion temperatures lead to the aggregation of free-machining phases, reducing machinability. Furthermore, Ni is also dissolved in Cu; excessive Ni can further increase material strength, resulting in significant tool wear during machining and negatively impacting machinability. Therefore, the Ni content is controlled to an upper limit of 1.8%, preferably 1.5%.
[0013] In can form a Bi-In free-machining phase with Bi. Compared to commonly used bismuth brass products, where elemental Bi readily exists as a Cu-Bi eutectic film in the copper matrix, the material exhibits poor cold and hot working properties. Furthermore, the abundant thin-film distribution of Bi does not significantly improve machinability. However, the addition of In results in a Bi-In free-machining phase with fine spherical particles, preventing the formation of thin films that deteriorate machinability and cold / hot working properties. The Bi-In phase also possesses excellent lubricity, reducing tool wear during machining and promoting improved cutting performance. Excessive In content significantly increases raw material costs and drastically reduces material plasticity, hindering effective extrusion and drawing processes. Therefore, the upper limit of In content is controlled at 0.15%, preferably 0.1%.
[0014] For ease of processing, preferably, the α phase ratio of the lead-free brass alloy is ≥80%.
[0015] Preferably, the Ni is added in the form of a Cu-Ni master alloy. Compared with adding elemental pure nickel, this can effectively reduce the melting temperature, thereby improving the melting efficiency and reducing the impact of high-temperature conditions on Zn burn-off and volatilization.
[0016] Preferably, the lead-free brass alloy has a tensile strength of 550–650 MPa, a yield strength of 350–500 MPa, an elastic modulus of 10–130 GPa, and a cutting index of not less than 90%. The average grain size of the α-phase is 2–20 μm; the average size of the Bi-In phase is 0.1–5 μm; the average size of the NiB compound is 0.01–1 μm; and the Bi-In phase particle distribution is 10,000–30,000 particles / mm.2 .
[0017] Preferably, the relaxation resistance of the lead-free brass alloy after being kept at 120°C for 24 hours is ≤30%.
[0018] The technical solution adopted by the present invention to solve the second technical problem mentioned above is: a method for preparing the above-mentioned lead-free brass alloy, characterized by comprising the following steps:
[0019] S1. Melting: The raw materials are placed in a melting furnace and heated to melt. The melting temperature is 950-1200℃.
[0020] S2. Casting: Horizontal continuous casting or semi-continuous casting is used to produce billets; electromagnetic stirring is employed, with a frequency of 20–50 Hz and a current of 80–120 A; the casting temperature is controlled at 1000–1100℃ to achieve the desired results. Cast billets of specified specifications, sawn to a length of 400–1000 mm;
[0021] S3. Extrusion: Before extrusion, the ingot is heated to a temperature of 600-700℃ and held for 1-4 hours. After heating, the ingot is placed in the extrusion cylinder for extrusion. The extrusion ratio is 100-350 and the extrusion speed is 3-15 mm / s to obtain the extruded billet. After extrusion, the billet is cooled, and the cooling rate of the extruded billet is controlled to be <200℃ / h.
[0022] S4. Annealing: The extruded billet is placed in a bell furnace or pit furnace for annealing heat treatment. The annealing temperature is 300-400℃ and the holding time is 1-4h to obtain the billet.
[0023] S5. Combined drawing: After the blank is pickled in the pickling tank, it is stretched, straightened and cut to length in the combined drawing equipment. The drawing rate is 10-20% and the drawing speed is 20-80m / min.
[0024] S6. Inspection and Warehousing: After the joint drawing is completed, a straightness inspection is carried out to control the straightness of the lead-free brass alloy to be <0.2mm / m.
[0025] If the heating temperature in step S3 is too low, the plasticity of the material under extrusion deformation will not meet the requirements, and the grains will not be thoroughly broken down and refined, leaving a certain amount of as-cast structure, which is not conducive to subsequent processing and obtaining good performance. If the heating temperature is too high, the grains will easily grow, the number of grain boundaries will be greatly reduced, resulting in a decrease in the number of easily machinable phases distributed within them, and the material's machinability will be reduced. At the same time, the material will soften severely under high-temperature heating conditions, which is not conducive to obtaining good elastic properties and relaxation resistance. Therefore, the heating temperature should be controlled at 600-700℃.
[0026] If the extrusion ratio is too small, the hot extrusion deformation of the material is insufficient, which can easily lead to the presence of large, residual cast grains and prevent the achievement of good microstructure uniformity and elastic properties. If the extrusion ratio is too large, the required extrusion pressure is greater, making material deformation more difficult and increasing tensile stress, which can easily lead to transverse periodic cracks. Therefore, when the extrusion ratio of S3 is between 100 and 350, the extruded billet has good surface quality and a fine, uniform equiaxed microstructure.
[0027] Under high-temperature extrusion conditions, a certain amount of β phase is retained within the material microstructure. By controlling the cooling rate of the extruded billet in step S3 to be <200℃ / h, and under the continuous high-temperature β→α phase transformation temperature, the amount of β phase is converted into α phase as much as possible, thereby improving the material's processing plasticity and increasing the uniformity of the microstructure. If the cooling rate of the extruded billet is too high, large-area continuous blocky β phase is easily formed, which increases the brittleness of the material on the one hand, and is particularly detrimental to the improvement of the material's machinability and elastic properties on the other hand.
[0028] In production, work hardening further improves the strength of the finished product. However, if the processing rate is further increased, the improvement in the material's mechanical properties, including elasticity and relaxation resistance, will approach its limit and will not be significantly improved. At the same time, controlling the straightness of the product becomes more difficult. Therefore, controlling the drawing speed to 20–80 m / min allows for good control of the finished product's surface quality and straightness while ensuring processing efficiency.
[0029] To reduce Zn element loss, preferably, the melting temperature of S1 is 980–1120°C.
[0030] Preferably, the microstructure of the ingot obtained by S2 is characterized by: an area ratio of elongated fibrous and columnar crystals <20%, a Bi-In phase size controlled to <10μm, and a Bi-In phase particle distribution of 6000–20000 particles / mm. 2 Reducing the formation of long, fibrous, and columnar crystals is beneficial for improving the uniformity of the microstructure in subsequent extrusion processes; at the same time, controlling the size of the Bi-In phase in the ingot is beneficial for improving the material's machinability.
[0031] Preferably, the axial and circumferential residual stress values of the blank after S4 annealing are both ≤100MPa. Annealing the extruded blank promotes the further precipitation and uniform distribution of NiB compounds in the matrix, improving the material's relaxation resistance and elasticity. On the other hand, it reduces and eliminates the residual stress in the extruded blank, ensuring that the axial and circumferential residual stress values of the resulting blank are both ≤100MPa. This improves the uniformity of properties in different parts of the blank, resulting in good straightness after drawing, reaching within 0.2mm / m.
[0032] Compared with existing technologies, the advantages of this invention are as follows: By adding a small amount of Bi, Bi and In form a Bi-In free-machining phase; ensuring that the material has excellent machinability under low Bi addition conditions, meeting the high-precision machining requirements of micron-level devices, without significantly deteriorating the material's cold and hot working properties and mechanical properties, and ensuring that the material obtains good elasticity and stress relaxation resistance; adding Ni improves the material's mechanical properties and ductility, and improves cold deformation working properties; adding B forms NiB compounds, further improving the material's yield strength and elastic properties; thus, the lead-free brass alloy possesses excellent machinability, stress relaxation resistance, elasticity, and cold and hot working properties; making it particularly suitable for applications in high-precision optical instruments. Attached Figure Description
[0033] Figure 1 This is a metallographic image of Embodiment 1 of the present invention;
[0034] Figure 2 This is a Bi-In phase distribution diagram of the finished product from Example 1 of the present invention;
[0035] Figure 3 This is a metallographic photograph of Comparative Example 2 of the present invention;
[0036] Figure 4 This is a particle distribution diagram of finished product B from Comparative Example 2 of the present invention. Detailed Implementation
[0037] The present invention will be further described in detail below with reference to the accompanying drawings and embodiments.
[0038] Example 1
[0039] like Figure 1 and 2 The image shown is a preferred embodiment of the present invention.
[0040] A lead-free brass alloy, the preparation method of which is as follows:
[0041] S1. Melting: Prepare the required components according to Table 1, and melt at a temperature of 1050℃.
[0042] S2. Casting: Billets are produced using horizontal continuous casting. Electromagnetic stirring is employed at a frequency of 20 Hz and a current of 100 A. The casting temperature is 1020℃, resulting in... Specifications: cast billet, sawn to a length of 500mm.
[0043] S3. Extrusion: Before extrusion, the ingot is heated to 680℃ and held for 3 hours. After heating, the ingot is placed in the extrusion cylinder for extrusion at an extrusion ratio of 210 and an extrusion speed of 13 mm / s. After extrusion, the billet is placed in a heat-insulating hood for slow cooling, controlling the cooling rate of the extruded billet to be <200℃ / h. The extruded specifications are obtained. blank.
[0044] S4. Annealing: Place the blank in a bell-shaped furnace or pit furnace for annealing heat treatment. Annealing temperature: 360℃, holding time: 4h.
[0045] S5. Combined Drawing: After thorough pickling in an acid pickling tank, the annealed blank is then stretched, straightened, and cut to length using a combined drawing machine. The drawing rate is 19%, and the drawing speed is 60 m / min. Finished bar stock.
[0046] S6. Inspection and Warehousing: After the finished product drawing process is completed, performance testing and analysis are carried out, and straightness inspection is performed. The straightness of the finished bar is <0.2mm / m.
[0047] Example 2
[0048] A lead-free brass alloy, the preparation method of which is as follows:
[0049] S1. Melting: Prepare the required components according to Table 1, and melt at 1100℃.
[0050] S2. Casting: Horizontal continuous casting is used to produce the billets, employing electromagnetic stirring at a frequency of 25 Hz and a current of 100 A. The casting temperature is 1030℃, and the resulting product... Specifications: cast billet, sawn to a length of 500mm.
[0051] S3. Extrusion: Before extrusion, the ingot is heated to 670℃ and held for 3 hours. After heating, the ingot is placed in the extrusion cylinder for extrusion at an extrusion ratio of 210 and an extrusion speed of 10 mm / s. After extrusion, the billet is placed in a heat-insulating hood for slow cooling, controlling the cooling rate of the extruded billet to be <200℃ / h. The extruded specifications are obtained. blank.
[0052] S4. Annealing: Place the blank in a bell-shaped furnace or pit furnace for annealing heat treatment. Annealing temperature: 350℃, holding time: 3h.
[0053] S5. Combined Drawing: After thorough pickling in an acid pickling tank, the annealed blank is then stretched, straightened, and cut to length using a combined drawing machine. The drawing rate is 19%, and the drawing speed is 70 m / min. Finished bar stock.
[0054] S6. Inspection and Warehousing: After the finished product drawing process is completed, performance testing and analysis are carried out, and straightness inspection is performed. The straightness of the finished bar is <0.2mm / m.
[0055] Example 3
[0056] A lead-free brass alloy, the preparation method of which is as follows:
[0057] S1. Melting: Prepare the required components according to Table 1, and melt at 1120℃.
[0058] S2. Casting: Billets are produced using horizontal continuous casting. Electromagnetic stirring is employed at a frequency of 30Hz and a current of 120A. The casting temperature is 1080℃, and the resulting product... Specifications: cast billet, sawn length 600mm.
[0059] S3. Extrusion: Before extrusion, the ingot is heated to 660℃ and held for 3 hours. After heating, the ingot is placed in the extrusion cylinder for extrusion at an extrusion ratio of 210 and an extrusion speed of 12 mm / s. After extrusion, the billet is placed in a heat-insulating hood for slow cooling, controlling the cooling rate of the extruded billet to be <200℃ / h. The extruded specifications are obtained. blank.
[0060] S4. Annealing: Place the blank in a bell-shaped furnace or pit furnace for annealing heat treatment. Annealing temperature: 330℃, holding time: 3h.
[0061] S5. Combined Drawing: After thorough pickling in an acid pickling tank, the annealed blank is then stretched, straightened, and cut to length using a combined drawing machine. The drawing rate is 19%, and the drawing speed is 70 m / min. Finished bar stock.
[0062] S6. Inspection and Warehousing: After the finished product drawing process is completed, performance testing and analysis are carried out, and straightness inspection is performed. The straightness of the finished bar is <0.2mm / m.
[0063] Example 4
[0064] A lead-free brass alloy, the preparation method of which is as follows:
[0065] S1. Melting: Prepare the required components according to Table 1, and melt at a temperature of 1000℃.
[0066] S2. Casting: Billets are produced using horizontal continuous casting. Electromagnetic stirring is employed at a frequency of 30Hz and a current of 80A. The casting temperature is 1000℃, and the resulting product... Specifications: cast billet, sawn length 700mm.
[0067] S3. Extrusion: Before extrusion, the ingot is heated to 680℃ and held for 2 hours. After heating, the ingot is placed in the extrusion cylinder for extrusion at an extrusion ratio of 158 and an extrusion speed of 7 mm / s. After extrusion, the billet is placed in a heat-insulating hood for slow cooling, controlling the cooling rate of the extruded billet to be <200℃ / h. The extruded specifications are obtained. blank.
[0068] S4. Annealing: Place the blank in a bell-shaped furnace or pit furnace for annealing heat treatment. Annealing temperature: 380℃, holding time: 3h.
[0069] S5. Combined Drawing: After thorough pickling in an acid pickling tank, the annealed blank is then stretched, straightened, and cut to length using a combined drawing machine. The drawing rate is 18.4%, and the drawing speed is 30 m / min. Finished bar stock.
[0070] S6. Inspection and Warehousing: After the finished product drawing process is completed, performance testing and analysis are carried out, and straightness inspection is performed. The straightness of the finished bar is <0.2mm / m.
[0071] Example 5
[0072] A lead-free brass alloy, the preparation method of which is as follows:
[0073] S1. Melting: Prepare the required components according to Table 1, and melt at 980℃.
[0074] S2. Casting: Billets are produced using horizontal continuous casting. Electromagnetic stirring is employed at a frequency of 50 Hz and a current of 100 A. The casting temperature is 1000℃, producing... Specifications: cast billet, sawn to a length of 500mm.
[0075] S3. Extrusion: Before extrusion, the ingot is heated to 620℃ and held for 4 hours. After heating, the ingot is placed in the extrusion cylinder for extrusion at an extrusion ratio of 158 and an extrusion speed of 11 mm / s. After extrusion, the billet is placed in a heat-insulating hood for slow cooling, controlling the cooling rate of the extruded billet to be <200℃ / h. The extruded specifications are obtained. blank.
[0076] S4. Annealing: Place the blank in a bell-shaped furnace or pit furnace for annealing heat treatment. Annealing temperature: 390℃, holding time: 3h.
[0077] S5. Combined Drawing: After thorough pickling in an acid pickling tank, the annealed blank is then stretched, straightened, and cut to length using a combined drawing machine. The drawing rate is 18.4%, and the drawing speed is 50 m / min. Finished bar stock.
[0078] S6. Inspection and Warehousing: After the finished product drawing process is completed, performance testing and analysis are carried out, and straightness inspection is performed. The straightness of the finished bar is <0.2mm / m.
[0079] Example 6
[0080] A lead-free brass alloy, the preparation method of which is as follows:
[0081] S1. Melting: Prepare the required components according to Table 1, and melt at a temperature of 1000℃.
[0082] S2. Casting: Billets are produced using horizontal continuous casting. Electromagnetic stirring is employed at a frequency of 45 Hz and a current of 110 A. The casting temperature is 1050℃, and the resulting product... Specifications: cast billet, sawn length 700mm.
[0083] S3. Extrusion: Before extrusion, the ingot is heated to 640℃ and held for 4 hours. After heating, the ingot is placed in the extrusion cylinder for extrusion at an extrusion ratio of 158 and an extrusion speed of 5 mm / s. After extrusion, the billet is placed in a heat-insulating hood for slow cooling, controlling the cooling rate of the extruded billet to be <200℃ / h. The extruded specifications are obtained. blank.
[0084] S4. Annealing: Place the blank in a bell-shaped furnace or pit furnace for annealing heat treatment. Annealing temperature: 400℃, holding time: 2h.
[0085] S5. Combined Drawing: After thorough pickling in an acid pickling tank, the annealed blank is then subjected to finished product stretching, straightening, and length-cutting processing on a combined drawing machine. The drawing rate is 18.4%, and the drawing speed is 40 m / min. Finished bar stock.
[0086] S6. Inspection and Warehousing: After the finished product drawing process is completed, performance testing and analysis are carried out, and straightness inspection is performed. The straightness of the finished bar is <0.2mm / m.
[0087] Comparative Example 1: HBi59-1 alloy purchased from the market.
[0088] Comparative Example 2: HBi58-1.5 alloy purchased from the market. Metallographic photographs and particle distribution diagrams of the finished product B are shown below. Figure 3 and 4 As shown.
[0089] The chemical composition of the lead-free brass alloys in all the above embodiments and comparative examples is shown in Table 1.
[0090] The mechanical properties and / or microstructure of the obtained examples and comparative examples were tested, and the final performance test results are shown in Tables 2-5.
[0091] The specific testing indicators and standards are as follows:
[0092] 1) Tensile strength, yield strength and elastic modulus test: Sample preparation and testing shall be carried out in accordance with Part 1 of GB / T 228.1-2010 "Metallic Materials - Tensile Testing": Room Temperature Tensile Test Method.
[0093] 2) Metallographic microscopic testing: Samples were prepared and tested according to YS / T 449-2002 "Inspection Method for Microstructure of Copper and Copper Alloy Castings and Processed Products".
[0094] 3) Cutting index: The cutting performance test method is evaluated according to Appendix B of YS-T 647-2007 "Copper-Zinc-Bismuth-Tellulose Alloy Rods". The cutting index of C36000 (HPb63-3) is set to 100%.
[0095] 4) Stress relaxation test: Sample preparation and testing shall be carried out in accordance with GB / T 39152-2022 "Test method for bending stress relaxation of copper and copper alloys".
[0096] Table 1 Chemical composition (wt%) of lead-free brass alloys in the examples and comparative examples
[0097]
[0098] Table 2 Microstructure characteristics of semi-finished products in the casting process of the examples.
[0099]
[0100]
[0101] Table 3 Microstructure properties of the finished products from the examples
[0102]
[0103] Table 4 Microstructure properties of comparative examples
[0104]
[0105] Table 5 Mechanical and cutting properties of finished products from the examples and comparative examples.
[0106]
[0107]
[0108] As shown in Tables 1-4, the properties of the brass alloy products of this invention are as follows: tensile strength: 550–650 MPa; yield strength: 350–500 MPa; elastic modulus: 110–130 GPa; average α-phase grain size: 2–20 μm; α-phase proportion ≥80%; average Bi-In phase size: 0.1–5 μm; average NiB compound size: 0.01–1 μm; Bi-In phase particle distribution: 10,000–30,000 particles / mm 2 After being kept at 120℃ for 24 hours, the relaxation rate was ≤30%. The microstructure uniformity of the example was better than that of the comparative example, and the amount of easily machinable phase was higher than that of the comparative example.
[0109] As shown in Table 3, all examples contain NiB compounds with well-controlled morphology and size, an α-phase ratio ≥80%, and small α-phase size, which is beneficial for improving material strength and relaxation resistance. Simultaneously, by controlling the size of the Bi-In phase, the examples achieve a more dispersed distribution of the Bi-In phase per unit area, thus improving the material's machinability.
[0110] As shown in Table 4, the yield strength and elastic modulus of the materials in the examples are higher than those in the comparative example, while the relaxation rate is lower, indicating that the products in the examples have superior resistance to deformation and relaxation during processing. Furthermore, the lead-free brass alloy of the examples exhibits better machinability than the comparative example. In addition, the tensile strength of the examples, ranging from 550 to 650 MPa, is also higher than that of the comparative example, demonstrating better processing plasticity of the lead-free brass alloy. This makes it particularly suitable for applications in high-precision optical instruments.
Claims
1. A lead-free brass alloy, characterized in that: The chemical composition (by mass percentage) of this lead-free brass alloy is: Cu: 53~60%; Bi: 0.1~0.8%; Ni: 0.05~1.8%; B:0.001~0.08%; In: 0.03~0.15%, balance is Zn and unavoidable impurities; The lead-free brass alloy has an α-phase ratio of ≥80%, and contains Bi-In phase and NiB compound. The average grain size of the α-phase is 2~20μm; the average size of the Bi-In phase is 0.1~5μm; the average size of the NiB compound is 0.01~1μm; and the Bi-In phase particle distribution is 10000~30000 particles / mm. 2 .
2. The lead-free brass alloy according to claim 1, characterized in that: The chemical composition (by weight percentage) of this lead-free brass alloy is: Cu: 55~58%; Bi: 0.2~0.6%; Ni: 0.1~1.5%; B:0.001~0.05%; In: 0.05~0.1%, balance is Zn and unavoidable impurities.
3. The lead-free brass alloy according to claim 1, characterized in that: The Ni is added in the form of a Cu-Ni master alloy.
4. The lead-free brass alloy according to claim 1, characterized in that: The lead-free brass alloy has a tensile strength of 550~650MPa, a yield strength of 350~500MPa, an elastic modulus of 10~130Gpa, and a cutting index of not less than 90%.
5. The lead-free brass alloy according to claim 1, characterized in that: The relaxation resistance of the lead-free brass alloy after being held at 120℃ for 24 hours is ≤30%.
6. A method for preparing the lead-free brass alloy according to any one of claims 1-5, characterized in that: Includes the following steps: S1. Melting: The raw materials are placed in a melting furnace and heated to melt. The melting temperature is 950~1200℃. S2. Casting: Horizontal continuous casting or semi-continuous casting is used to produce billets; electromagnetic stirring process is used, frequency: 20~50HZ, current: 80~120A; casting temperature is controlled at 1000~1100℃, and billets with specifications of φ100~300mm are produced, with a sawing length of 400~1000mm. S3. Extrusion: Before extrusion, the ingot is heated to a temperature of 600~700℃ and held for 1~4 hours. After heating, the ingot is placed in the extrusion cylinder for extrusion. The extrusion ratio is 100~350 and the extrusion speed is 3~15mm / s. The extruded billet is obtained, and the billet is cooled after extrusion, with the cooling rate of the extruded billet controlled to be <200℃ / h; S4. Annealing: The extruded billet is placed in a bell furnace or pit furnace for annealing heat treatment. The annealing temperature is 300~400℃ and the holding time is 1~4h to obtain the billet. S5. Combined drawing: After the blank is pickled in the pickling tank, it is stretched, straightened and cut to length in the combined drawing equipment. The drawing rate is 10~20% and the drawing speed is 20~80m / min. S6. Inspection and Warehousing: After the joint drawing is completed, a straightness inspection is carried out to control the straightness of the lead-free brass alloy to be <0.2mm / m.
7. The method for preparing the lead-free brass alloy according to claim 6, characterized in that: The melting temperature of S1 is 980~1120℃.
8. The method for preparing the lead-free brass alloy according to claim 6, characterized in that: The microstructure of the ingot obtained by S2 is characterized by: the area ratio of elongated fibrous and columnar crystals <20%, the size of the Bi-In phase controlled at <10μm, and the distribution of Bi-In phase particles at 6000~20000 / mm. 2 .
9. The method for preparing the lead-free brass alloy according to claim 6, characterized in that: The residual stress values in both the axial and circumferential directions of the blank after S4 annealing are ≤100MPa.
Citation Information
Patent Citations
Lead-free free-cutting bismuth brass alloy material for mobile phone lens
CN113337754A
High-performance bismuth brass alloy material for mobile phone lens
CN115198137A
Environment-protective lead-free brass and preparation method thereof
CN104109774A
Brass alloy bar and preparation method thereof
CN116219223A
Lead-free free-cutting aluminium brass alloy and its manufacturing method
EP2208802A1
